Deep Sea Drilling Program Site 77-540 bulk carbonate stable isotope, grain size, and X-ray fluorescence data across the Eocene/Oligocene Boundary, southern Gulf of Mexico - Patricia Standring; Christopher M Lowery; Rowan C Martindale (PANGAEA, 2025)
This dataset contains analysis of Deep Sea Drilling Program Site 540 sediment cores from the southeastern Gulf of Mexico from the late Eocene to the early Oligocene. The data include bulk carbonate stable carbon (δ13C) and oxygen (δ18O) isotopes values. Stable isotopes were measured on a Gasbench II coupled to a Thermo MAT253 isotope ratio mass spectrometer in the Stable Isotope Laboratory at the University of Texas at Austin and reported VPDB. Additional data are grain size measurements acquired from a laser grain size analyzer (Malvern Mastersizer 3000), and X-Ray Fluorescence (XRF) data acquired on the third-generation XRF scanner at the Gulf Coast Repository at Texas A&M University. XRF data were measured at ~5 cm resolution at 10kv and 30kV and quality controlled by removing data with positive Ar values, which indicate air was measured rather than the sediment core surface.